TESTING MARKET ANOMALIES ON ABNORMAL RETURNS AND TRADING VOLUME ACTIVITY FOR LQ45 INDEX - Ni Luh Putu Yulia Paramita; Sayu Ketut Sutrisna Dewi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Market anomalies are unanticipated events that provide investors with opportunities to achieve abnormal returns. The January Effect and Monday Effect are two seasonal anomalies often exploited by investors to gain abnormal returns in the capital market. This study aims to investigate the impact of the January Effect and the Monday Effect on abnormal returns and trading volumes on Mondays and in the months before and after January for LQ45 stocks on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The study population consists of 63 issuers, with a sample of 25 selected through purposive sampling. The analysis uses the Paired Sample T-test, Wilcoxon Signed Rank Test, and One- Sample Test processed with SPSS software.The analysis reveals that the January Effect causes abnormal returns in 2019, 2020, and 2021, but not in 2022 and 2023. Trading volume showed no significant differences during the observation period. For the Monday Effect, significant average abnormal returns are observed on Mondays in 2020, 2021, and 2023, but not in 2019 and 2022. Trading volume on Mondays also shows significant differences across the observation period. These findings suggest that investors should consider market anomalies when making investment decisions.